Would Collective Action Clauses Raise Borrowing Costs? An Update and Additional Results - Eichengreen, Barry; Mody, Ashoka (World Bank, Washington, DC, 2014)
It is easy to say that the International Monetary Fund should not resort to financial rescue for countries in crisis; this is hard to do when there is no alternative. That is where collective action clauses come in. Collective action clauses are designed to facilitate debt restructuring by the principals - borrowers, and lenders - with minimal intervention by international financial institutions. Despite much discussion of this option, there has been little action. Issues of bonds fear that collective action clauses would raise borrowing costs. The authors update earlier findings about the impact of collective action clauses on borrowing costs. It has been argued that only in the past year or so, have investors focused on the presence of these provisions, and that, given the international financial institutions' newfound resolve to "bail in" investors, they now regard these clauses with trepidation. Extending their data to 1999, the authors find no evidence of such changes, but rather the same pattern as before: Collective action clauses raise the costs of borrowing for low-rated issuers, but reduce them for issuers with good credit ratings. Their results hold both for the full set of bonds and for bonds issued only by sovereigns. They argue that these results should reassure those who regard collective action clauses as an important element in the campaign to strengthen international financial architecture.